Women and the politics of place - Harcourt, Wendy, 1959-; Escobar, Arturo, 1951- (Bloomfield, CT : Kumarian Press, 2005)
"This book analyzes the mobilization of women's economic and social justice movements by challenging traditional views"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Women -- Political activity; Women in development; Human body -- Social aspects; Place (Philosophy); Marginality, Social; Social movements; Women -- Social conditions